HAK ASASI MANUSIA DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 16 TAHUN 2011 TENTANG BANTUAN HUKUM - Suprijatna, Dadang (DERECHTSSTAAT, 2016)
Â This study aims to answer how the implementation of legal aid as access to justice for poor people? And any obstacles encountered in the implementation of legal aid? From the results of studies conducted with methods and rules of studies in jurisprudence showed that the implementation of legal aid for people who could not be implemented properly for their deviations in practice, such as the implementation of legal assistance through mentoring new advocate can be enjoyed by the public at the time of inspection advanced not at the time of the initial inspection and the inspection process is ongoing, but without the presence of lawyers, can still be found action advocates who refuse to provide legal aid, as advocates considered less professional and discrimination in the implementations of legal aid. The factors inhibiting the implementation of legal aid for poor people can be classified and divided into three factors namely, the factor of the substance of the law, a factor legal structure, and the cultural factors of law or culture of the community and law enforcement agencies, such as the lack of public understanding of the right to legal aid refers on mistrust, pessimism and skepticism towards the implementation of legal aid, and elements of attitudes, values, ways of acting and thinking advocates leading to the attitudes or actions of irregularities. Factors that inhibit community is negative community views on the implementation of legal aid as well as concerns in the use of legal aid.